Digitalisation and challenges of the education system: project work in formation of foreign language communicative competence - S. N. Orlova; S. V. Firsova (Вестник университета)
The paper deals with some aspects of project-based learning application in the formation of students’ communicative competence as a new model of digital transformation of the education system. The authors focus on the development and dissemination of the project-based learning method within frameworks of the discipline “Foreign language” as a new model of the work of educational organisations. The methods used in the research conducted for this article represent a combination of modern information resources use and online technologies in teaching foreign languages in a non-linguistic university. Thus, project work becomes a learning technology that allows modelling communication within the educational process to obtain the required educational results in a digital educational environment, and for increasing motivation for learning.